Apoptotic activity of substituted 3-O-acetyl-betulinic acid benzylamides - Marie Kozubek; Linda Höhlich; Sophie Hoenke; Hans-Peter Deigner; Ahmed Al-Harrasi; René Csuk (Elsevier, 2021)
Acetylated betulinic acid (BA) was converted into mono-substituted benzylamides 2-14. Screening in SRB assays showed them as cytotoxic for a variety of different human tumor cell lines. While parent BA was not cytotoxic within the limits of the assay (cut-off 30 ​μM), the target amides were cytotoxic. Their bioactivity as well as their tumor cell/non-tumor cell selectivity depended on the substitution pattern of the aromatic ring. The most active compound 9 (holding an ortho methoxy substituent) acted mainly by apoptosis.